Structure and function of type IV IRES in picornaviruses: a systematic review - Li, Yan; Zhang, Lei; Wang, Ling; Li, Jing; Zhao, Yanwei; Liu, Fuxiao; Wang, Qianqian (Frontiers in Microbiology, 2024)
The Picornaviridae is a family of icosahedral viruses with single-stranded, highly diverse positive-sense RNA genomes. Virions consist of a capsid, without envelope, surrounding a core of RNA genome. A typical genome of picornavirus harbors a well-conserved and highly structured RNA element known as the internal ribosome entry site (IRES), functionally essential for viral replication and protein translation. Based on differences in their structures and mechanisms of action, picornaviral IRESs have been categorized into five types: type I, II, III, IV and V.Compared with the type IV IRES, the others not only are structurally complicated, but also involve multiple initiation factors for triggering protein translation. The type IV IRES, often referred to as hepatitis C virus (HCV)-like IRES due to its structural resemblance to the HCV IRES, exhibits a simpler and more compact structure than those of the other four. The increasing identification of picornaviruses with the type IV IRES suggests that this IRES type seems to reveal strong retention and adaptation in terms of viral evolution. Here, we systematically reviewed structural features and biological functions of the type IV IRES in picornaviruses. A comprehensive understanding of the roles of type IV IRESs will contribute to elucidating the replication mechanism and pathogenesis of picornaviruses.